Analisis Kondisi Jalan Rel Kereta Api Pada Lintas Sragen-Solo Berdasarkan Nilai Track Quality Indeks (TQI) - Muhtarom, Zaini; Ratih, Silvia Yulita (Jurnal Teknik Sipil, 2021)
One way to keep the train service flow runs safely, maintenance of railroad geometry is required. Maintenance of railroad tracks uses the Track Quality Index assessment to determine which railroad compartments or corridors are prioritized for repair. The research method used is a quantitative research method. The calculation of the TQI of railroad tracks includes force, height, spoor width and lining. The results of the calculation of the TQI value (manual) give the cumulative total number of standard deviation index is 21.6. While the TQI calculation (mechanical) total cumulative number index standard deviation is 21.2. Based on the results of the TQI calculation, the condition of the railroad tracks can be classified into the criteria for the TQI level II (standard deviation of 20 - 35), namely that the railroad can be passed by trains at speeds of 80-100 km/hour. The railroad maintenance based on the TQI is the repairs to rail compartments or corridors that experience leveling damage in segment 9, lining damage in segment 7, wide damage spoor (gauge) in segments 5,7 and 10 and elevation damage (cant) in segment 3.